Measuring CIS Health Systems Using the Stochastic Frontier Analysis (SFA) - Yesilyurt, Ozgur; Selamzade, Fuad (Economy of Regions, 2020)
The Commonwealth of Independent States (CIS) was founded in 1991 after the dissolution of the Union of Soviet Socialist Republics (USSR). The member countries are Azerbaijan, Belarus, Armenia, Kazakhstan, Kyrgyzstan, Moldova, Uzbekistan, Russia, Tajikistan, Turkmenistan and Ukraine. Turkmenistan resigned its full membership status in 2005 and changed its CIS standing to observer member. Drawing on the methods of Least Squares and Maximum Likelihood Estimation of Stochastic Frontier Analysis, we made estimations to find efficiency scores in the health sector by using the data for the period from 2010 to 2015 of the coun- tries that are members of the Commonwealth of Independent States. In the study, we used various factors as dependent and independent variables, including the number of doctors, medical personnel and hospital beds per ten thousand people, the life expectancy at birth, under-five mortality rate and the incidence of tuberculosis per one hundred thousand people. We have found that such factor as the number of doctors effectively influences reduction of the under-five mortality rates and the incidence of tuberculosis, while the factor “the number of hospital beds” is not very effective. Finally, for the CIS countries we made recommendations to popularize the health insurance, to change the old Soviet form of health management in public hospitals, and to implement liberal socio-economic policies.